Rapamycin treatment induces tubular proteinuria: role of megalin-mediated protein reabsorption - Peres, Rodrigo A. S.; Peruchetti, Diogo B.; Silva-Aguiar, Rodrigo P.; Teixeira, Douglas E.; Gomes, Carlos P.; Takiya, Christina M.; Pinheiro, Ana Acacia S.; Caruso-Neves, Celso (Frontiers in Pharmacology, 2023)
Introduction: Rapamycin is an immunosuppressor that acts by inhibiting the serine/threonine kinase mechanistic target of rapamycin complex 1. Therapeutic use of rapamycin is limited by its adverse effects. Proteinuria is an important marker of kidney damage and a risk factor for kidney diseases progression and has been reported in patients and animal models treated with rapamycin. However, the mechanism underlying proteinuria induced by rapamycin is still an open matter. In this work, we investigated the effects of rapamycin on parameters of renal function and structure and on protein handling by proximal tubule epithelial cells (PTECs). Methods: Healthy BALB/c mice were treated with 1.5 mg/kg rapamycin by oral gavage for 1, 3, or 7 days. At the end of each treatment, the animals were kept in metabolic cages and renal function and structural parameters were analyzed. LLC-PK1 cell line was used as a model of PTECs to test specific effect of rapamycin. Results: Rapamycin treatment did not change parameters of glomerular structure and function. Conversely, there was a transient increase in 24-h proteinuria, urinary protein to creatinine ratio (UPCr), and albuminuria in the groups treated with rapamycin. In accordance with these findings, rapamycin treatment decreased albumin-fluorescein isothiocyanate uptake in the renal cortex. This effect was associated with reduced brush border expression and impaired subcellular distribution of megalin in PTECs. The effect of rapamycin seems to be specific for albumin endocytosis machinery because it did not modify renal sodium handling or (Na++K+)ATPase activity in BALB/c mice and in the LLC-PK1 cell line. A positive Pearson correlation was found between megalin expression and albumin uptake while an inverse correlation was shown between albumin uptake and UPCr or 24-h proteinuria. Despite its effect on albumin handling in PTECs, rapamycin treatment did not induce tubular injury measured by interstitial space and collagen deposition. Conclusion: These findings suggest that proteinuria induced by rapamycin could have a tubular rather than a glomerular origin. This effect involves a specific change in protein endocytosis machinery. Our results open new perspectives on understanding the undesired effect of proteinuria generated by rapamycin.